Entrepreneurship successfully launching new ventures - Barringer, Bruce R.; Ireland, R. Duane (Pearson Education Limited, 2022)
Entrepreneurship: Successfully Launching New Ventures explores the allure of entrepreneurship, teaching students how to successfully launch and grow their own business. Using real business profiles of inspiring young entrepreneurs, the text engages students through relevant examples they can easily relate to. The 6th Edition examines entrepreneurship through an easy, four-step process that clearly outlines both the excitement and difficulty of launching a new company. Careful to identify failures as well as successes, the text is a guide to starting a new business.